Topological phases in nanoparticle monolayers: can crystalline, hexatic, and isotropic-fluid phases coexist in the same monolayer? - Bhattacharjee, Kaustav; Vaidya, Salil S.; Pathak, Tushar; Shimpi, Jayesh R.; Prasad, Bhagavatula L. V. (Soft Matter, 2023)
Topological phases are stable configurations of matter in 2-dimensions (2D) formed via spontaneous symmetry breaking. These play a crucial role in determining the system properties. Though a number of fundamental studies on topological phase transitions and topological defect dynamics have been conducted with model colloidal systems (typically microns in size), the same is lacking on nanoparticle monolayers (NPMLs, typically made of ligand-coated sub-ten nanometer particles). Here, we show that in an evaporation-driven self-assembly process, the three topological phases, namely crystalline, hexatic, and isotropic-fluid phases, can coexist within the same NPML. We associate this coexistence with the local variation in particle size, which can be described by a unique frequency parameter (p(25)), quantifying the fraction of NPs that has size deviation greater than or equal to 25% of the mean size (where the deviation,f is defined as f = ((|Size-mean|)/mean)). The p(25)-values for the three phases are distinctly different: crystalline arrangement occurs when p(25) < similar to 0.02, while a hexatic phase exists for 0.02 <= p(25) <= 0.1. For p(25) Z 0.1, the isotropic-fluid phase occurs. Following KTHNY-theory, we further numerically extrapolate the occurrence of each phase to the accumulated excess planar strain in the NPML due to the presence of various topological defects in the structures.

Tailoring of rheological properties through hydrophobic interactions in silica-based liquid crystal gels - Sumana, S.; Chakrabortty, Pratyasha; Karumuthil, Subash Cherumannil; Prasad, S. Krishna; Prasad, Bhagavatula L. V. (ChemPhysChem, 2025)
Modification of the intrinsic hydrophilic character of the pristine silica nanoparticles (SiNP) decorated with silanol moieties into a hydrophobic state has been of substantial interest, owing to the amenability to gelation of desirable liquids. Many reports exist on composites of SiNP with liquid crystals (LCs), an epitome of anisotropic soft matter. The fumed SiNP, unlike its precipitated counterpart, has been the preferred variety. A family of colloidal gel systems is reported, consisting of precipitated SiNP in a nematic LC, formed by substituting some native silanols with methyl, butyl, or dodecane chains. Detailed steady state and oscillatory rheological measurements are performed, along with analyses using the soft glass and other viscoelastic models. The study demonstrates that the sophisticated modified fractional models, Kelvin-Voight and Maxwell, proposed for generalized viscoelastic behavior of soft materials, are quite successful in describing these nematic gels as well. The observed nontrivial relationship between the ligand length and the strength of the gel network is elucidated on the basis of a judicious combination of the van der Waals, hydrogen bonding, and hydrophobic interactions, leading to a detailed understanding of the viscoelastic behavior of the composites and the influence of SiNP surface chemistry.
Keywords: fractional viscoelastic models; Hydrophobic; nematic; rheological studies; silica nanoparticles